A fluorescent probe for the quantification of heparin in clinical samples with minimal matrix interference - Szelke, Helga; Schübel, Sarah; Harenberg, Job; Krämer, Roland (Chemical communications, 2010)
A red-fluorescent perylene diimide probe allows sensitive quantification of heparin, a widely used antithrombotic drug, in plasma and serum samples with minimal interference from matrix components.